Bíbí in Berlin. Education and confirmation - Stefánsdóttir, Guðrún V.; Ólafsdóttir, Sólveig; Magnússon, Sigurður Gylfi (Netla, 2022)
Bíbí is a nickname for Bjargey Kristjánsdóttir, an Icelandic woman who was born in 1927 and died in 1999. She grew up on a small farm called Berlin in northern Iceland. Bíbí fell seriously ill when she was in her first year and after that she was labelled ‘feebleminded’ by her family and local community. In her early years, Bíbí was excluded within the local community and hidden from visitors at her home. Her autobiography, however, evinces intelligence and insight into her life and circumstances. The autobiography is a huge work, totaling about 120,000 words. Bíbí wrote her autobiography alone, keeping it secret from her family and neighbors. In this chapter, Bíbí’s childhood story will be analysed based on two research disciplines: critical disability studies and microhistory. By connecting these two research fields, we will subsequently provide a new way of critical thinking about disability as well as history. A feminist intersectionality framework is used to analyse Bíbí’s childhood story; more specifically to explore how social class, disability and gender intersected and afflicted Bíbí’s childhood life and education.The main aim of this chapter is twofold. Firstly to shed light on Bíbí’s childhood, especially her education and confirmation. On the other hand, the goal is to explore various official records, such as church records, parish registers and annual reports. As well as explaining various events in Bíbí’s life, those documents also elucidate the spirit of the age and the perspectives of the community she was brought up in. We also wish to clarify how the scientific knowledge and dominant ideology about people with intellectual disabilities influenced and shaped Bíbí’s life and circumstances. Bíbí’s autobiography clearly reflects the influence of the grand narrative of eugenics and the medical understanding of disability (Carlson, 2010). As a result, Bíbí was marginalised and experienced many forms of exclusion and oppression. Bíbí was definitely unaware, as were other members of the community in ...